Exclusive Image Gallery on Human Spinal Cord Regeneration-Clinical Image-55 - Giselher Schalow (Imaging Journal of Clinical and Medical Sciences - Peertechz Publications, 2019)
Two ways to get up from the floor after falling. In A through D mainly the arms are used for getting up and in E through H the legs.